2004
DOI: 10.1093/jhered/esh083
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Inheritance of White Spotting and the Evaluation of KIT and EDNRB as Spotting Loci in Dutch Boxer Dogs

Abstract: The genetic basis of the white spotting pattern in Dutch boxer dogs is not known. We studied whether the segregation of white spotting in boxers follows a Mendelian inheritance pattern. Blood samples were collected, along with digital photographs in standard directions of (grand)parents (n=16) and offspring (n=52) from eight litters of Dutch boxers. In order to select heterozygous parents, we selected nonuniform litters, in which at least one puppy was extreme white. On the basis of criteria for the location, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…USP31 and RBBP6 have been shown to be strongly associated with late onset deafness in border collies. EDNRB is probably responsible for deafness in lethal white foal syndrome ( 117 , 187 ) and deafness in BEW American Paint and pinto horses ( 118 ). Mutations in MITF were shown to be responsible for deafness in a Franches-Montagnes colt ( 189 ) and in German Fleckvieh cattle ( 201 ), Chinese Rongchang pigs ( 203 ), and Hedlund white American mink ( 210 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…USP31 and RBBP6 have been shown to be strongly associated with late onset deafness in border collies. EDNRB is probably responsible for deafness in lethal white foal syndrome ( 117 , 187 ) and deafness in BEW American Paint and pinto horses ( 118 ). Mutations in MITF were shown to be responsible for deafness in a Franches-Montagnes colt ( 189 ) and in German Fleckvieh cattle ( 201 ), Chinese Rongchang pigs ( 203 ), and Hedlund white American mink ( 210 ).…”
Section: Discussionmentioning
confidence: 99%
“…There was 100% identity in the sequences of the two dogs, suggesting that KIT plays no role in deafness in Dalmatians. van Hagen et al ( 117 ) evaluated KIT and EDNRB to better understand white spotting in boxers, but found no association with the genes and white spotting; hearing status was not considered, but there is a high prevalence of deafness in white boxers. EDNRB (OMIM entry 131244) is acted on by endothelin 3 to act on the MAPK pathway to act on posttranslational Mitf (Figure 2 ), and EDNRB mutations are associated with lethal white foal syndrome in horses ( 118 ) and deafness in American Paint horses ( 119 ).…”
Section: Deafness In Domestic Animal Speciesmentioning
confidence: 99%
“…They excluded both EDNRB and KIT as the gene causing the white underside markings seen in most Border Collies which segregated as an autosomal recessive trait in Newfoundland–Border Collie backcross families. Similarly, these genes were excluded for the white markings seen in Boxers (van Hagen et al. 2004).…”
Section: Spotting Patterns and White Markingsmentioning
confidence: 99%
“…Nevertheless, it does not appear to be responsible for these patterns in dogs (Metallinos & Rine ; Van Hagen et al . ), where it was found that the microphthalmia‐associated transcription factor ( MITF ) gene is implicated in spotted phenotypes (Karlsson et al . ).…”
Section: Family Material Markers and Genotypingmentioning
confidence: 99%